A study on the applicability of Kirton adaption-innovation theory in the local context using undergraduates from Nanyang Technological University as subjects - Leow, Wee Leng (2014)
Previous research identified that cognitive personality style of an individual affects the way he/she "appraises problems" and the "type of solutions produced". In addition, this style is said to remain stable even with training.